Long-Acting Beta 2 Agonists Suppress IP-10 Expression in Human Bronchial Epithelial Cells. (1st October 2012) - Chien, Jien-Wen; Chu, Yu-Te; Yang, San-Nan; Kuo, Chang-Hung; Wang, Wei-Li; Kuo, Po-Lin; Jong, Yuh-Jyh; Hung, Chih-Hsing
Abstract : Background: Interferon-γ-inducible protein (IP)-10 (CXCL10) is an important chemokine secreted by the airway epithelium that functions as a biomarker for virus-induced asthma. Long-acting beta 2 (β2 ) agonists (LABAs) are frequently used as inhaled medication for asthma and chronic obstructive pulmonary disease. However, previous research failed to investigate the effects of LABAs on IP-10 in bronchial epithelial cells. Objective: To study the effects and signaling pathways of formoterol and salmeterol on polyriboinosinic polyribocytidylic acid (poly I:C)-induced IP-10 expression in BEAS-2B cells. Methods: BEAS-2B cells were pretreated with formoterol and salmeterol for 2 hours before poly I:C stimulation. ICI 118551 (β2 adrenoreceptor antagonist) or mitogen-activated protein kinase (MAPK) inhibitors were added 30 minutes before LABAs were added. Enzyme-linked immunosorbent assay and real-time polymerase chain reaction were used to measure IP-10 protein and messenger RNA levels. Mitogen-activated protein kinase inhibitors and Western blotting were used to identify MAPK pathways, whereas bioassay revealed the MAPK functions. Results: Long-acting β2 agonists significantly down-regulated the poly I:C-induced IP-10 protein and messenger RNA expression in BEAS-2B cells. ICI 118551 reversed this effect. Forskolin, a cyclic adenosine monophosphate activator, produced a similar inhibitory effect. Western blotting showed that formoterol suppressed poly I:C-induced IP-10 expression via the c-Jun N-terminal kinase–c-Jun pathway. Conclusion: Long-acting β2 agonists down-regulate poly I:C-induced IP-10 expression in BEAS-2B cells via the β2 adrenoreceptor–cyclic adenosine monophosphate and c-Jun N-terminal kinase/c-Jun pathways. Long-acting β2 agonists also inhibit IP-10 production in bronchial epithelial cells and may prolong viral elimination.